(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
In this article, the efficiency of obtaining female calves by insemination with female seeds of the Black-Ola cattle breed cows, which are kept on a large scale by the population of our country, is presented. The live weight of cows bred with same-sex seeds, the characteristics of seed retention, and growth indicators were studied.